Surface Engineering Methods for Powder Bed Printed Tablets to Optimize External Smoothness and Facilitate the Application of Different Coatings - Khanh T. T. Nguyen; Daan Zillen; Franca F. M. van Heijningen; Kjeld J. C. van Bommel; Renz J. van Ee; Henderik W. Frijlink; Wouter L. J. Hinrichs (MDPI AG, 2023)
In a previous attempt to achieve ileo-colonic targeting of bovine intestinal alkaline phosphatase (BIAP), we applied a pH-dependent coating, the ColoPulse coating, directly on powder bed printed (PBP) tablets. However, the high surface roughness necessitated an additional sub-coating layer [Nguyen, K. T. T., Pharmaceutics 2022]. In this study, we aimed to find a production method for PBP tablets containing BIAP that allows the direct application of coating systems. Alterations of the printing parameters, binder content, and printing layer height, when combined, were demonstrated to create visually less rough PBP tablets. The addition of ethanol vapor treatment further improved the surface's smoothness significantly. These changes enabled the direct application of the ColoPulse, or enteric coating, without a sub-coating. In vitro release testing showed the desired ileo-colonic release or upper-intestinal release for ColoPulse or enteric-coated tablets, respectively. Tablets containing BIAP, encapsulated within an inulin glass, maintained a high enzymatic activity (over 95%) even after 2 months of storage at 2-8 °C. Importantly, the coating process did not affect the activity of BIAP. In this study, we demonstrate, for the first time, the successful production of PBP tablets with surfaces that are directly coatable with the ColoPulse coating while preserving the stability of the encapsulated biopharmaceutical, BIAP.